Cultura e afetividade: um estudo da influência dos processos de enculturação e aculturação matemática na dimensão afetiva dos alunos - Diogo Alves de Faria Reis (2008)
This study identifies the degree to which mathematics learning approximates either to a process of enculturation or to a process of acculturation (Bishop 1988, 2002a). We examine the practices of two secondary Mathematics teachers, in terms of Bishops notion of acculturator-teacher, and the students affective reactions, which they expressed both in relation to their learning and responses to their teachers practice. These reactions are examined in terms of beliefs (Gómez Chacón, Op t Eynde & De Corte 2006), background feelings (Damasio 1996, 2004) and attitudes (Brito & Gonçalez 2001). The researcher acted as participant observer in the manner of ethnography and data were collected by: a) audio and video recorder of a sequence of mathematics lessons, b) audio recorder of interviews with the students, c) audio and written registers of observations in class. Data are presented to support our arguments and conjectures. We conclude by discussing two main pedagogical implications resulting from the study: 1) teachers' practices showed being characterized by other relevant aspects, such as the supportive and affective ways in which the teachers assist their students, that go beyond the scope of the notion of acculturator-teachers, 2) teachers values viewed in terms of the processes of enculturation and acculturation - have a powerful (negative or positive) influence on the students affect. This influence (or the students affect) is not sufficiently discussed in the research field of teachers professional development.